Estudo numérico da estabilidade elástica de placas de aço enrijecidas utilizando a geometria clothoidal como enrijecedor - Jorge Fernando dos Reis (2021)
The use of elements characterized as slender steel plates is common in the structural design of civil construction projects, justified by their high mechanical strength, weight reduction and efficient material consumption. Therefore, this work presents a comparative analysis, by means of the Finite Element Method (FEM), of the elastic stability of stiffened plates with flat and clothoidal stiffeners, the latter format being normally used as a shear connector in composite steel and concrete structural elements. The study evaluates cases with different normal stress ratios, stiffener positions, relative bending stiffness, aspect ratio between panel sides, and different patterns of the clothoidal shape, controlled by the ex step. In addition, these variations are also considered for the case of models subjected to pure shear. In general, it was found that for high stiffness values, i.e., so the stiffener behaves as rigid, there are no significant differences in the behavior of the panel. Nevertheless, when lower ranges of stiffness are considered, the models with clothoidal stiffeners present improved performance when compared to the conventional flat design, indicating that the clothoidal geometric portion confers increased stiffness to the stiffener as a function of its ex step. Thus, an iterative process was conducted in order to define an equation that established a relationship between the clothoidal section to an equivalent flat portion as a function of the parameter ex, which proved to be functional for all parameters analyzed in the study. Finally, the results of the analysis concluded that clothoidal shaped stiffeners can be used conservatively as if they were flat, considering only the flat part, or with better material utilization using the equivalent width increment equation proposed in this work.